The Influence of the Photographs of the Civil Rights Movement on the Advancement of the Movement The Case of Emmett Till Murder and Birmingham Campaign - FADLI ,Hadji; Kaid,Nassima (Faculty of Letters and Foreign Languages Department of English, 2017)
The present study attempts to shed light on the role and the contribution of photography in advancing the Civil Rights Movement in the United States. The beginning of the movement, and the succession of the events, mainly the Birmingham campaign(1963), inspired the leaders of the struggle to involve qualified photographers to cover the direct actions, conduct the different associations and groups of activists, like sit-ins and marches. The movement adopted the non-violence philosophy, where protestors and marchers met to desegregate any public place. The peaceful calm protests of African Americans were usually opposed by violent intervention of the police forces. So the result was a set of insane harmful scenes of black citizens beaten by policemen, and here the importance of photographers, whose the job was to document and report this violence, and to unveil these sufferings to the public opinion. The importance of photography was so significant in the Civil Rights Movement, on the one hand, it gave an opportunity to the activists of the movement to see themselves as it reflected the reality of the American society. On the other hand, it made pressure on the government to react effectively in order to stop segregation against the African Americans